An Interpretation of Consolation of the Mind From the Perspective of Ecocriticism - Liu, Dongfeng (Journal of Theory and Practice of Social Science, 2023)
The comfort of the mind, as the representative work of the natural culture, Williams in the comfort of the mind, in the 1980 s the great salt lake in Utah and bear river migratory birds reserve is destroyed, and cancer by against the current, grandmother family women, such as the author of how to cope with the dual pain and seek peace of mind. Through a unique narrative perspective, the tragedy of the female family is connected with the experience of the Great Salt Lake, so as to call for human attention to nature and show the overall ecological values of man and nature. From the perspective of ecological judgment, this paper explores the criticism of anthropocentrism in the book and conveys the thoughts of ecological feminism.